Relaxin as a potential diagnostic biomarker for ovarian cancer- A prospective study. (May 2021) - Gkrozou, F.; Pappa, C.; Tsonis, O.; Dimitriou, E.; Paschopoulos, M.
Abstract: Ovarian cancer is a leading cause of female mortality worldwide. Although novel approaches on this disease have been developed, overall survival rates remain moderate due to the lack of scientific evidence promoting screening at early stages of the disease. A number of biomarkers have been suggested as predictive for this type of cancer. The role of relaxin in endometrial cancer is well documented but the scientific evidence is lacking with regards to ovarian cancer. We studied patients with ovarian cancer, benign ovarian cyst and healthy patients too. The levels of relaxin have been found to be an adequate diagnostic biomarker for ovarian cancer. We also presented the different range of Ca125, HE4 and ROMA in these three groups. Randomised control trials need to be conducted though, in order to elucidate the true role of relaxin in these cases.